Severity of carbohydrate metabolism disturbances, arterial hypertension stage, and lipid profile in patients with metabolic syndrome - Yu. V. Zhernakova; I. E. Chazova; S. P. Olimpieva; V. V. Kilikovskyi (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To investigate the associations between the severity of carbohydrate metabolism disturbances, arterial hypertension (AH) severity (based on AH stage and 24-hour blood pressure monitoring (BPM) parameters), and lipid profile. Material and methods. In 403 patients with AH and metabolic syndrome (MS), blood biochemical assay, glucose tolerance test, and 24-hour BMP were performed. Results. Patients with impaired glucose tolerance (IGT), compared to participants with impaired fasting glycemia (IFG) or particularly to individuals with normal carbohydrate metabolism, demonstrated more severe lipid profile disturbances, more advanced AH stage, and increased mean BP levels, BP load, and BP variability at 24-hour BPM. Conclusion. IGT, as a more severe variant of carbohydrate metabolism disturbances, could be associated with increased risk of cardiovascular disease and Type 2 diabetes mellitus.